Core-Satellite Supraparticles to Ballistically Stamp Nanostructures on Surfaces - Oppmann, Maximilian; Miller, Franziska; Thuerauf, Sandra; Groppe, Philipp; Prieschl, Johannes; Stauch, Claudia; Mandel, Karl (ACS Applied Materials and Interfaces, 2018)
Nanostructured surfaces are of great importance in a very wide range of fields. They can be obtained by imprint or deposition techniques. However, these are usually sophisticated to perform. Generally, it is not easy to equip an object/product with a nanostructure after manufacturing. Yet, it would be very beneficial to achieve a modification of an arbitrary surface with a nanostructure of choice at a later stage by an approach that is simple to perform without the need of sophisticated equipment or excessive treatment by physicochemical methods. Herein, such a process is reported, which combines two "old-fashioned" techniques, namely, sandblasting and rubber-stamping, and translates them to the "nanoworld". By creating core-satellite supraparticles via spray-drying, a ballistic core-satellite stamp particle system is obtained, which can be used to easily transfer a wide range of nanoparticles to a great variety of surfaces to equip these with a nanostructure and subsequently advanced properties. These include water-repellant, antifouling, or antidust surfaces. Moreover, it is also demonstrated that the approach can be used to manufacture well-defined nanoimprinted surfaces. Such surfaces showed an improved spreading behavior for aliphatic alcohols, thus making such surfaces, for instance, very susceptible for disinfectants. All in all, the simple technique described herein has a great potential for creating nanostructured surfaces on nearly any surface.
CRIS-Team Scopus Importer:2020-04-02
Keywords: coatings; imprint; nanostructures; sandblasting; supraparticles; surface modification